2017
DOI: 10.1111/cge.13012
|View full text |Cite
|
Sign up to set email alerts
|

A nonsense mutation in CEP55 defines a new locus for a Meckel‐like syndrome, an autosomal recessive lethal fetal ciliopathy

Abstract: Mutations in genes involved in the cilium-centrosome complex are called ciliopathies. Meckel-Gruber syndrome (MKS) is a ciliopathic lethal autosomal recessive syndrome characterized by genetically and clinically heterogeneous manifestations, including renal cystic dysplasia, occipital encephalocele and polydactyly. Several genes have previously been associated with MKS and MKS-like phenotypes, but there are still genes remaining to be discovered. We have used whole-exome sequencing (WES) to uncover the genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 51 publications
4
60
0
Order By: Relevance
“…The polarized form of cytokinesis in embryonic cortical NSCs is poorly understood, but may influence the segregation of organelles and apical fate determinants to daughter cells as they make fate choices. Recent findings that mutations in Kif20b and other midbody genes cause microcephaly in humans and mice suggest that brain development is especially sensitive to defects in cytokinesis (26,(35)(36)(37)(38)(39). To elucidate these issues, we developed methods to quantitatively analyze furrowing and abscission in NSCs of the developing cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The polarized form of cytokinesis in embryonic cortical NSCs is poorly understood, but may influence the segregation of organelles and apical fate determinants to daughter cells as they make fate choices. Recent findings that mutations in Kif20b and other midbody genes cause microcephaly in humans and mice suggest that brain development is especially sensitive to defects in cytokinesis (26,(35)(36)(37)(38)(39). To elucidate these issues, we developed methods to quantitatively analyze furrowing and abscission in NSCs of the developing cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Using a zebra fish model, they demonstrated that loss of function of cep55 mimicked the features of MARCH observed in human patients, therefore establishing a strong connection of the protein with a novel multiple congenital anomaly syndrome. Bondeson et al (46) showed that loss of Cep55 is associated with a ciliopathic lethal autosomal recessive syndrome called MKS, characteristics of which involve renal cystic dysplasia, occipital encephalocele, and polydactyly.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we showed that Akt was destabilized in the homozygous mutants, which was partially rescued by providing either constitutively activated PI3K-CA or AKT1 expression. In addition, 2 recent studies have emphasized the connection between CEP55 loss and genetic diseases like multinucleated neurons, anhydramnios, renal dysplasia, cerebellar hypoplasia, and hydranencephaly (MARCH) (45) and Meckel-Gruber syndrome (MKS) (46), characterized by the presence of multiple congenital anomalies.…”
mentioning
confidence: 99%
“…Abscission, the process through which the membrane connecting the two newly generated cells is severed resulting in physical separation of the siblings, concludes cytokinesis . Few studies have directly examined cytokinesis in NSCs and RGCs during corticogenesis despite mutations of cytokinesis‐regulating proteins in several neurodevelopmental disorders (e.g., microcephaly) . In polarized tissues such as the telencephalon, the orientation of division may be critical to maintain overall tissue structure and daughter cell identity .…”
Section: Cortical Development Neural Stem Cells and Cytokinesismentioning
confidence: 99%